Fortress of the Muslim : Invocations from the Quran and Sunnah - Complied by Said bin Ali bin Wahf Al-Qahtani and Translation Revised by Aqeel Walker (Lahore Darussalam, 2003)
A pocket-size collection of 266 supplications in English, Arabic, with transliteration for easy reading in Arabic and the circumstances listed appropriate for each dua.
Keywords: Hadith -- Texts